Analysis of the relationship of the learning video with students 'understanding of learning materials - Yulyani Arifin; Diana Syarifah Permai; Dicky Hida Syahchari; Raharto Condrobimo (Social Economics and Ecology International Journal (SEEIJ), 2021)
The aim of the study was to examine the relationship between the relationship between instructional videos and students' understanding of the learning material. Researchers create digital learning materials through video material (VBL), especially math in RPTRA. The researchers used correlation analysis to examine the relationship between the learning material in video form and the level of understanding of the students in the material. The method used by the researcher was to experiment with elementary-level children from various primary schools. Then, based on the experimental results, the correlation analysis test was performed to see the relationship between the student's understanding and the learning material through video. From the results of the assessment, it can be seen that the video material can help the understanding of the students and can also increase the motivation of the students in learning mathematics. Therefore, video learning can help students understand mathematics and help teachers teach mathematics in a more interesting way.